HBV-Specific CD8+ T-Cell Tolerance in the Liver - Baudi, Ian; Kawashima, Keigo; Isogawa, Masanori (Frontiers in Immunology, 2021)
Hepatitis B virus (HBV) remains a leading cause of liver-related morbidity and mortality through chronic hepatitis that may progress to liver cirrhosis and cancer. The central role played by HBV-specific CD8+ T cells in the clearance of acute HBV infection, and HBV-related liver injury is now well established. Vigorous, multifunctional CD8+ T cell responses are usually induced in most adult-onset HBV infections, while chronic hepatitis B (CHB) is characterized by quantitatively and qualitatively weak HBV-specific CD8+ T cell responses. The molecular basis of this dichotomy is poorly understood. Genomic analysis of dysfunctional HBV-specific CD8+ T cells in CHB patients and various mouse models suggest that multifaceted mechanisms including negative signaling and metabolic abnormalities cooperatively establish T cell dysfunction. Immunoregulatory cell populations in the liver, including liver resident dendritic cells (DCs), hepatic stellate cells (HSCs), myeloid-derived suppressor cells (MDSCs), may contribute to intrahepatic T cell dysfunction through the production of soluble mediators, such as arginase, indoleamine 2,3-dioxygenase (IDO) and suppressive cytokines and the expression of co-inhibitory molecules. A series of recent studies with mouse models of HBV infection suggest that genetic and epigenetic changes in dysfunctional T cells are the manifestation of prolonged antigenic stimulation, as well as the absence of co-stimulatory or cytokine signaling. These new findings may provide potential new targets for immunotherapy aiming at invigorating HBV-specific CD8+ T cells, which hopefully cures CHB.